Preliminary study of online training implementation from multiple perspectives in Malaysian public sectors - Mohd. Asarani, N. A. (Asian Research Publishing Network, 2016)
In a constantly changing and evolving global and organizational environment, it is necessary to improve the skills of human resources. The innovation of information technologies nowadays has contributed to the exponential expansion in online training in Malaysia. The number employees attending online training courses have increased tremendously but very low percentage of course completion have been reported, thus raised many questions in the implementation of online training in Malaysian public sectors. This study was conducted to construct a research framework on online training implementation in Malaysian public sectors. The criteria of online training implementation are also being determined through different perception of stakeholders. Based on the literature review, the study posited four constructs adopted from Kirkpatrick’s learning theory through Multiple Perspectives Theory. The preliminary study conducted involves 3 set of interviews with respondents involved in providing online training at Malaysia’s National Institute of Public Administration (INTAN) as providers or consultants of public sectors online training. The preliminary findings showed that the criteria are applicable with the mentioned criteria in the literature review thus suitable to be mapped into the conceptual framework.